A data structure for graph to facilitate hiding of information in a graph's segments – a graph theoretic approach to steganography. (29th June 2009) - Kumar, Vinay; Muttoo, Sunil Kumar
In this paper, we present a data structure that is suitable for graph representation that can be used as a cover object in steganography. Steganography is a science of hiding information with the purpose of making the information unreadable by a third party. The information is placed in the cover object in such a way that the distortion introduced in the cover object is as minimal as possible and to the extent not recognisable by the human eye. To accomplish the task, redundancy in the representation of the cover object is identified before placing the information in it. There exists a number of data structure for graph representation e.g., adjacency matrix, incidence matrix, adjacency list, etc. These classical data structures allow little scope of finding redundancy in graph. The data structure presented in this paper is file based. It divides a graph into three components: node, segment and intermediate points that constitute a segment. Under the scheme, only planar graph is being considered to maintain clarity in spatial representation of a graph. The presented data structure is aimed to facilitate graph theoretic approach to steganography.